Inovasi Produk Kopicek (Kopine Wong Picek) Sebagai Upaya Pemberdayaan Kelompok Difabel Tunanetra Mata Hati - Pradana, Bagus Cahyo Shah Adhi; Farhanindya, Hikmah Husniyah; Ardiana, I Dewa Ketut Raka (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
Coffee is an important commodity with significant global demand. In Indonesia, East Java Province contributed 85.15% of the national coffee production in the Large Estate sector in 2022, supporting the growth of the local coffee industry such as coffeeshops. In Surabaya, the Mata Hati Community, consisting of people with disabilities, launched a coffee brand called "Kopicek" as an effort to empower disabled individuals, especially the blind. However, they face challenges in terms of quality control, manual production processes, and limited promotion. To carry out and create innovations in empowering the visually impaired or the blind, our team provides mentoring and training to improve the quality and efficiency of Kopicek's production. Through a community service program, the social service team designed solutions to improve the quality and efficiency of Kopicek's production. These solutions include quality control training, provision of automated coffee machines and custom packaging press machines that are accessible to blind baristas, as well as digital marketing training. The results of this program are expected to help the Mata Hati Community maintain coffee product consistency, expand marketing through digital media, and enhance Kopicek's branding in the local market.